State and Societal Challenges in the Horn of Africa - Alexandra Magnólia Dias (dir.) (Centro de Estudos Internacionais, 2013)
This book brings to fruition the research done during the CEA-ISCTE project ''Monitoring Conflicts in the Horn of Africa'', reference PTDC/AFR/100460/2008. The Portuguese Foundation for Science and Technology (FCT) provided funding for this project. The chapters are based on first-hand data collected through fieldwork in the region's countries between 4 January 2010 and 3 June 2013. The project's team members and consultants debated their final research findings in a one-day Conference at IS...